Multimodal Imaging for Total Anomalous Systemic Venous Drainage Diagnosis and Preoperative Planning: A Case Report and Literature Review - Ding, Mingyan; Zhang, Huihui; Sun, Dandan; Li, Qiang; Jiao, Ni; Zhu, Fang (Frontiers in Cardiovascular Medicine, 2022)
Total anomalous systemic venous drainage (TASVD) is a rare congenital heart malformation. Here, we report a case of a 40-year-old male patient who had a total anomalous systemic venous drainage. It was diagnosed as the TASVD for the first time through multimodal imaging combined Transthoracic (TTE), transesophageal (TEE) and three-dimensional (3D-TTE) echocardiography, contrast echocardiography and computed tomography angiography (CTA). We review 15 published reports on TASVD and summarize the ultrasonographic characteristics. After intracardiac repair through ectopic venous drainage in cardiac surgery, the patient's cyanosis symptoms were alleviated greatly. Echocardiography was the first-line examination for TASVD. Multimodal imaging combined TTE, TEE, 3D TEE, contrast echocardiography and CTA was necessary for confirmed diagnosis of TASVCD.